Economic Operation for V2G Technology and Multiple Influence Factors Extraction of EV Penetration - Yanqing Qu (Energy Science & Engineering)
ABSTRACT Electric vehicles (EVs) are likely to have a continuing presence in the vehicle market all over the world for the next few decades. The rapid development of large‐scale applications of EVs in China has provided a foundation for the implementation of vehicle‐to‐grid (V2G) technology. V2G can help EVs participate in grid regulation services. Based on the economic model of EV integration with the grid, the regulation ability and potential economic and environmental benefits brought by EV high penetration are analyzed using relevant data from Shanghai. Analysis results show that EV participation with V2G capability can not only reduce EV expenditures but also provide peak load‐shifting service. Further analyses show that with the increase of EV charging power and peak‐valley electricity price ratio and the decrease of battery loss cost, the economic benefits of V2G applications will increase. The large‐scale development of EVs also can effectively reduce CO2 emissions according to the model proposed.